The interaction between serves and match winning in table tennis players in the London 2012 Olympic Games - Katsikadelis, M.; Pilianidis, T.; Mantzouranis, N. (International Journal of Table Tennis Sciences, 2013)
The serve is a unique shot which is closely related to the player`s technical and tactical strategy. The aim of this study was to assess the interaction between the serves and the match winning in high-ranking table tennis players. The sample consisted of 16 male and 16 female players who participated in the top-16 round in the single tournaments of the London 2012 Olympic Games. The chi square (÷2) was firstly generated to analyze the mean values from the top-16 matches in relation to the gender. The Pearson`s analysis was applied for the evaluation of the inter-correlation among the playing variables, while the factor analysis assessed the possible advantage of the serves win points during the matches. All statistical analyses were carried out with the SPSS-PASW 18.0 for Windows. From the results it is shown that the evaluated parameters did not differ in relation to the gender. The Pearson`s coefficient presented that the earned points from the serves were significantly correlated with the overall playing performance in both male (r = 0.98, p < 0.001) and female (r = 0.96, p < 0.001) high-qualified table tennis players. Thus, the factor analysis confirmed that, with an accuracy of 93% to 94% in male and female world-class players, the successful serves lead to the win of the match regardless the number of the played games. In addition, the qualitative analysis of the winning points, when the players served, ranged between 62 % and 67 % in men and women medal winners respectively. In conclusion, the winning outcome in table tennis matches is strongly related to the successful serves of the world-class players. The findings of this study, which presented the serves advantage in the playing performance, could be valuable for the training orientation of the table tennis players.